Optimisation on the stability of CaO-doped partially stabilised zirconia by microwave heating. Issue 6 (15th March 2021) - Ling, Yeqing; Li, Qiannan; Zheng, Hewen; Omran, Mamdouh; Gao, Lei; Chen, Jin; Chen, Guo
Abstract: Partially stabilised zirconia has advantages for the applications in the metallurgical processes which have special requirements in corrosion resistance and high-temperature performance. In the present work, controllable microwave heating was used for the uniform thermal field and consequent microstructure improvement to further improve the stability of partially stabilised zirconia, which was 88.14% prepared by electric arc melting. Analyses including X-ray diffraction (XRD), Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy (Raman) were used to study the effect of temperature change on the phase composition and structure of the samples. After heating at temperatures of 900 °C, 1000 °C, 1100 °C, 1200 °C and 1300 °C for 1h, the stabilities of the heated product were 88.51%, 95.02%, 95.17%, 96.31% and 97.64%, respectively. From the phase transformations based on the experimental results, the discussion indicates that the martensitic transformation temperature of zirconia from m-ZrO2 to t-ZrO2 during the heating stage was reduced under the radiation of microwave energy.